Perturbations in small molecule synthesis uncovers an iron-responsive secondary metabolite network in Aspergillus fumigatus - Wiemann, Philipp; Lechner, Beatrix E.; Baccile, Joshua A.; Velk, Thomas A.; Yin, Wen-Bing; Bok, Jin Woo; Pakala, Suman; Losada, Liliana; Nierman, William C.; Schroeder, Frank C.; Haas, Hubertus; Keller, Nancy P. (Frontiers in Microbiology, 2014)
Iron plays a critical role in survival and virulence of the opportunistic pathogen Aspergillus fumigatus. Two transcription factors, the GATA-factor SreA and the bZip-factor HapX oppositely monitor iron homeostasis with HapX activating iron acquisition pathways (e.g. siderophores) and shutting down iron consumptive pathways (and SreA) during iron starvation conditions whereas SreA negatively regulates HapX and corresponding pathways during iron sufficiency. Recently the non-ribosomal peptide, hexadehydroastechrome (HAS; a tryptophan-derived iron (III)-complex), has been found important in A. fumigatus virulence. We found that HAS overproduction caused an iron starvation phenotype, from alteration of siderophore pools to regulation of iron homeostasis gene expression including sreA. Moreover, we uncovered an iron dependent secondary metabolism network where both SreA and HapX oppositely regulate multiple other secondary metabolites including HAS. This circuitry links iron-acquisition and consumption pathways with secondary metabolism - thus placing HAS as part of a metabolic feedback circuitry designed to balance iron pools in the fungus and presenting iron availability as one environmental trigger of secondary metabolism.